The innovative approach to relationships with customers - Korsakienė, Renata (Journal of Business Economics and Management, 2009)
Customer relationship management is a relatively new discipline, which became popular in the last decade. It has to be noted that customer relationship management is oriented toward current customers and allows to attract new customers. Therefore, customer relationship management is related to long‐term success in the market. The paper analyses infrastructure, institutional and internal issues which restrict customer relationship management in Lithuanian real estate companies. Presented investigation is based on questioning of real estate companies which encounter the problems of economy slowdown.First Publish Online: 14 Oct 2010